Criminal Law Study on Narcotics Abuse Rehabilitation - Widiasyam, Salma; Haris, Oheo; Abdullah, Siti Aisah (IJCLS (Indonesian Journal of Criminal Law Studies), 2020)
The purpose of this research is to determine whether the rehabilitation of the victims of narcotics abuse in the decree of the District Court of Kendari No. 236/Pid. Sus/2019/PN K has fulfilled the element of Article 54 Act number 35 year 2009. The type of research used in this study is normative research, using the Statute Approach, Case Approach, Conceptual Approach.Based on the results the authors conclude that narcotic addicts and narcotics abuse victims are obliged to undergo medical rehabilitation and social rehabilitation. The judge in the its verdict prosecute convicted because it has been proven legally and committed guilty of committing a criminal offence "narcotic abuse for himself", dropping a criminal against the defendant with imprisonment for 1 (one) year and 2 (two) months have in accordance with article 127 paragraph (1) of Law No. 35 Year 2009. However, in the ruling judge ignores article 127 paragraph (2) and paragraph (3) of Law No. 35 Year 2009 that the obligation of the judge in providing rehabilitation efforts against the defendant cases of drug abuse in line with the issuance of Circular Letter of Supreme Court No. 4 Year 2010.